2010
DOI: 10.1126/scitranslmed.3001002
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Integrin-Specific Ligands Enhance Tissue Healing and Biomaterial Integration

Abstract: Engineered biointerfaces covered with biomimetic motifs, including short bioadhesive ligands, are a promising material-based strategy for tissue repair in regenerative medicine. Potentially useful coating molecules are ligands for the integrins, major extracellular matrix receptors that require both ligand binding and nanoscale clustering for maximal signaling efficiency. We prepared coatings consisting of well-defined multimer constructs with a precise number of recombinant fragments of fibronectin (monomer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
151
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(151 citation statements)
references
References 38 publications
(61 reference statements)
0
151
0
Order By: Relevance
“…Several studies have shown that ECM ligand spacing regulates FA and stress fiber assembly, cell spreading and migration, and adhesive forces (Massia and Hubbell, 1991 Coussen et al, 2002;Koo et al, 2002;Jiang et al, 2003;Arnold et al, 2004;Cavalcanti-Adam et al, 2007;Petrie et al, 2010;Selhuber-Unkel et al, 2010). However, whether the geometric organization of the ECM ligand regulates FA assembly and force transmission has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have shown that ECM ligand spacing regulates FA and stress fiber assembly, cell spreading and migration, and adhesive forces (Massia and Hubbell, 1991 Coussen et al, 2002;Koo et al, 2002;Jiang et al, 2003;Arnold et al, 2004;Cavalcanti-Adam et al, 2007;Petrie et al, 2010;Selhuber-Unkel et al, 2010). However, whether the geometric organization of the ECM ligand regulates FA assembly and force transmission has not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that both ECM rigidity and ligand spacing influence FA and stress fiber assembly, cell spreading, migration speed, and adhesive forces (Massia and Hubbell, 1991;García et al, 1998a;Maheshwari et al, 2000;Wang et al, 2001;Coussen et al, 2002;Koo et al, 2002;Jiang et al, 2003;Arnold et al, 2004;Griffin et al, 2004;Engler et al, 2006;CavalcantiAdam et al, 2007;Petrie et al, 2010;Selhuber-Unkel et al, 2010). For instance, different average minimal RGD ligand spacings are required for spreading (440 nm) and FA assembly (140 nm) (Massia and Hubbell, 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that cells can exert traction forces through cadherin cell-cell contacts (42,43), so hydrogel mechanics and the loading environment may need to be considered in the utility of such materials. It has also been shown that cluster presentation of certain mimetic peptides, such as those containing an integrin-binding Arg-Gly-Asp (RGD) domain, significantly increases their binding efficacy (44,45). Therefore, the local presentation (e.g., clustering and tether length) may be optimized independent of hydrogel mechanics to further mimic and present the molecule for cellular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the fragment had better osteointegration in vivo than the RGD sequence, suggesting that integrin specificity is relevant, as different integrins bind to RGD and FMIII7-10. Additionally, the importance of integrin clustering was shown using monomer, dimer, trimer, and pentamers of FMIII7-10 [189]. Studies have yet to be done to investigate if polymer brush coatings can enhance osteointegration under diseased states such as osteoporosis.…”
Section: Controlling Cell-materials Interactions With Modified Brushesmentioning
confidence: 99%